Seven deadly economic sins : obstacles to prosperity and happiness every citizen should know - Otteson, James R. (Cambridge : Cambridge University Press, 2021)
You have heard of the Seven Deadly Sins: pride, greed, lust, envy, gluttony, wrath, and sloth. Each is a natural human weakness that impedes happiness. In addition to these vices, however, there are economic sins as well. And they, too, wreak havoc on our lives and in society. They can seem intuitively compelling, yet they lead to waste, loss, and forgone prosperity. In this thoughtful and compelling book, James Otteson tells the story of seven central economic fallacies, explaining why they are fallacies, why believing in them leads to mistakes and loss, and how exorcizing them from our thinking can help us avoid costly errors and enable us to live in peace and prosperity.
Wealth is positive-sum -- Good is not enough -- There is no great mind -- Progress is not inevitable -- Economics and/or morality -- Equality of what? -- Markets are not perfect -- Conclusion: The world and I.
Title from publisher's bibliographic system (viewed on 09 Apr 2021).
Keywords: elektronické knihy; electronic books; Economics -- Moral and ethical aspects; Economics -- Sociological aspects